Synthesis-in-place of V2O5 nanobelts for wide range humidity detection - Cho, Sungjin; Lim, Si Heon; Oh, Jaeyeon; Ju, Tae-Seong; Yang, Seungmo; Kim, Hyun Ho; Kim, Yeonhoo (Sensors and actuators. B, Chemical, 2025)
Resistive type humidity sensors offer advantages in simplicity, low cost, compact size, and remote operation. Due to the benefits, they have great potential for use in a variety of environments and future applications, including the Internet of Everything (IoE). However, resistive humidity sensors have limitations in detecting extreme humidity levels below 10 % or above 90 % relative humidity (RH) and are also vulnerable to high temperatures, which hinders their use in harsh environments applications. For broader applications, humidity sensors with reliable performance across the full range of humidity levels and high stability at elevated temperatures need to be developed. Here, we report high performance resistive humidity sensors based on V2O5 nanobelts operating at high temperatures. The V2O5 nanobelts are directly deposited between Pt electrodes by O2-assisted physical vapor transport (PVT) method. The V2O5 nanobelt humidity sensor exhibits reliable humidity sensing properties over a wide range from 1 % to 100 % RH. Furthermore, long-term stability and reproducibility of V2O5 nanobelts are demonstrated through 25 consecutive humid air pulses and measurements obtained after 4 months of storage. The high performance of the V2O5 nanobelt humidity sensor is advantageous for practical use in applications ranging from IoE environments to harsh industrial conditions. •Synthesis-in-place V2O5 nanobelts were fabricated by physical vapor transport method.•The V2O5 nanobelt sensor shows high sensitivity to low humidity range from 1 % to 10 %.•The sensor demonstrates excellent long-term stability over 4 months.•The synthesis-in-place sensor exhibits high stability at elevated temperatures